Penguatan Kelompok Tuna Rungu Gerkatin Kalbar Melalui Pelatihan Digital Marketing Untuk Inklusi Digital - Arninda Arninda; Syarifah Putri Agustini; Istikoma Istikoma; Rangga Aditya Saputra; Fathia Aliya Supandih; Roni Roni (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
The Community Partnership Program (PKM) aims to strengthen the capacity of the West Kalimantan Gerkatin disability group through digital marketing training to support inclusive digital transformation. Implemented by the Muhammadiyah University of Pontianak, this activity addresses partner issues related to weak financial management and limited access to digital marketing. Solutions provided include training in financial management, product photography, social media marketing, AI-based copywriting, and assistance in creating an online store via WooCommerce. On September 13 and 20, 2025, 35 deaf participants participated in the training with the support of a Sign Language Interpreter. As a result, 60% of participants were able to prepare financial reports, 75% understood digital marketing, and 70% produced catalog-worthy product photos and descriptions. The implementation of the program encountered challenges associated with participants’ limited baseline digital literacy; however, these were mitigated through intensive mentoring and the application of accessible, disability-friendly technologies. The program also produced a prototype website for cacatjualan.com and various outputs such as journal articles, media publications, videos, posters, and training materials that support the achievement of activities, particularly poverty alleviation, decent work, inequality reduction, and support for the university's Key Performance Indicators in the field of community service. The impact is seen in improving digital skills, social inclusion, and the economic potential of disability groups.